Effect of Gastrointestinal Hemorrhage on Outcome After Endovascular Treatment in Acute Basilar Artery Occlusion - Zhang, Hao; Dai, Weipeng; Kong, Weilin; Duan, Zhenhui; Yun, Zongjin; Zhou, Sheng; Yang, Jie; Li, Fengli; Zi, Wenjie; Guo, Zhangbao; Liu, Wenhua (Frontiers in Neurology, 2022)
Background and Purpose: Gastrointestinal hemorrhage (GIH) is associated with poorer prognosis and higher mortality after acute ischemic stroke, but its association with outcomes after endovascular treatment (EVT) was unclear. This study aimed to assess the incidence, risk factors, and the relationships with clinical outcomes of GIH after EVT in patients with acute basilar artery occlusion (BAO). Methods: Consecutive patients treated with EVT were identified from the EVT for Acute Basilar Artery Occlusion Study (BASILAR) registry. All included patients were divided into GIH and non-GIH subgroups, and the independent predictors of GIH after EVT were explored. An ordinal logistic regression model was used to assess the association between GIH and primary outcome (distribution of modified Rankin scale) at 90 days, and binary logistic regression models for other outcomes. Results: Among 647 patients, 114 (17.6%) patients experienced GIH after EVT. Higher glucose on admission, longer procedure time, and general anesthesia were the independent predictors of GIH after EVT, while the posterior circulation Acute Stroke Prognosis Early Computed Tomography Score (pc-ASPECTS) ≥5 and history of hyperlipidemia were protective factors. Compared with non-GIH, GIH was associated worse functional outcome (adjusted common OR, 2.12 [95% CI, 1.39-3.25]), lower rates of functional independence (adjusted OR, 0.47[95% CI, 0.26-0.88]) and favorable outcome (adjusted OR, 0.41[95% CI, 0.22-0.73]), and higher risk of 90-day mortality (adjusted OR, 1.76 [95% CI, 1.08-2.85]). Conclusion: GIH is not uncommon after EVT in patients with acute BAO, and is associated with worse functional disability and higher mortality.